Single phase matrix converter (SPMC) for boost inverter operation / Norlizawati Abdul Manap - Abdul Manap, Norlizawati (2007)
This paper presents development of boost DC-AC converter based on the SPMC topology which is known as an advanced topology that could perform many different converter functions. The boost DC-AC converter naturally generates an output AC voltage lower or larger than DC input voltage. A computer simulation model was developing to study the behavior of the proposed converter by using the Power System Block Set (PSB) within the MATLAB/Simulink (MLS) environment. The switching strategy were used that will result in the input source of the SPMC which then converted to the desired output. Based on the duty cycle, the output was synthesized. The basic AC-AC SPMC topology was used as a reference circuit by changing the switching of the driver circuit of IGBT to convert it to boost DC-AC converter. The simulation result of MATLAB/Simulink is presented.